The Imagery and Symbolism Analysis of the Novel “Sister Carrie” by Theodore Dreiser - Dilnoza, Sharafutdinova (European Journal of Life Safety and Stability (2660-9630), 2023)
In this article Theodore Dreiser has discussed the consequences of the life of the main character of novel “Sister Carrie”, paying attention on the social reasons for Carrie’s fall, on her spiritual condition in the life struggle against the backdrops of social phenomena. During the research process, it was discovered that one of the novel’s important elements is the realization that Carrie will never be satisfied with what she has; she will constantly yearn for more. Carolina Meeber, unable to wait for one, is already reaching for another, unable to be satisfied with what she already has. Carrie’s life discontent with stems from the fact, that she never truly enters “high society”. She never had that woman happiness and true love.